Corporate governance in the 2007–2008 financial crisis: Evidence from financial institutions worldwide - Erkens, David H.; Hung, Mingyi; Matos, Pedro (Journal of Corporate Finance, 2012)
This paper investigates the influence of corporate governance on financial firms' performance during the 2007–2008 financial crisis. Using a unique dataset of 296 financial firms from 30 countries that were at the center of the crisis, we find that firms with more independent boards and higher institutional ownership experienced worse stock returns during the crisis period. Further exploration suggests that this is because (1) firms with higher institutional ownership took more risk prior to the crisis, which resulted in larger shareholder losses during the crisis period, and (2) firms with more independent boards raised more equity capital during the crisis, which led to a wealth transfer from existing shareholders to debtholders. Overall, our findings add to the literature by examining the corporate governance determinants of financial firms' performance during the 2007–2008 crisis.